Design, manufacturing and testing of parachute recovery system for aludra SR-10 unmanned aerial vehicle (UAV) - Saim, Raudhah (2019)
Unmanned Systems Technology (UST) Aludra SR-10 Unmanned Aerial Vehicle (UAV) was purposely designed for survey and mapping mission. This study focuses on the design, manufacturing and testing of Parachute Recovery System (PRS) on the Aludra SR-10 UAV. A design work of PRS involving in defining a suitable type of parachute design, parachute compartment, parachute deployment and activation mechanism system. This study was performed by simulation approach (using Computational Fluid Dynamic, CFD) and experimental approach (static drop test and flight test). The evaluation of aerodynamics characteristics using ANSYS software over two types of parachute models (annular and cruciform parachutes canopy) help to determine the most suitable type of parachute design for PRS. The static drop test with on board system (consisted of NI myRio, IMU and GPS) programme using LabVIEW software was performed to evaluate the feasibility of the parachute. Meanwhile, the flight test was conducted to investigate the performance and reliability of PRS at different deployment heights. A baseline annular parachute canopy with 2.41 m of the nominal diameter was selected as the main parachute, which produced highest drag coefficient (1.03). The findings also highlighted the significance of separation and recirculating flows behind studied geometries, which in turn was responsible in producing the drag. Through the static drop test, the selected parachute design provided a predicted terminal descent velocity of approximately 4 m/s with payload of 5kg. This parachute recovery system was able to reduce the impact force at fourth time lower compared to belly landing, from 139.77 N to 30.81 N. The pilot-chute was successful pulled main parachute to free stream and fully inflated in a short time, less than 3 seconds. Most of all, the parachute recovery was able to support and bring the aircraft to a soft and safe landing thus, confirmed its reliability. Interestingly, robust evidence in a prediction of the landing position area using PRS was achieved.